2017
DOI: 10.1002/msc.1195
|View full text |Cite
|
Sign up to set email alerts
|

Recovery‐stress patterns and low back pain: Differences in pain intensity and disability

Abstract: The findings indicate an association between detrimental recovery-stress patterns and LBP. Examining the role of recovery has innovative practical relevance for LBP prevention and rehabilitation through the implementation of approaches to enhance recovery in relevant programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Several studies using different approaches to search for subgroups among CLBP patients were found. Solovieva et al [59], Tegeder et al [60], Karpinnen et al [61], Costigan et al [62] for example, found subgroups based on genetic factors, while Turk et al [63], Turk [64], Dahlstrom et al [65], Turk et al [66], Johansson et al [67], Turk et al [68], Soderlund et al [69], Thieme et al [70], Widerström-Noga et al [71], Heidari et al [72] found subgroups based on psychosocial factors, and Huijen et al [73], McCracken et al [74], Hasenbring et al [75] based subgroups on activity-related behavior. As all CLBP patients had a back pain diagnosis in common, it seemed logical to cluster these patients based on their pain characteristics as well as psychological and social factors, as was done by Waddell [7], Hasenbring et al [75], Foster [76], Kamper [77], and Wettstein et al [78] in various previous cluster analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using different approaches to search for subgroups among CLBP patients were found. Solovieva et al [59], Tegeder et al [60], Karpinnen et al [61], Costigan et al [62] for example, found subgroups based on genetic factors, while Turk et al [63], Turk [64], Dahlstrom et al [65], Turk et al [66], Johansson et al [67], Turk et al [68], Soderlund et al [69], Thieme et al [70], Widerström-Noga et al [71], Heidari et al [72] found subgroups based on psychosocial factors, and Huijen et al [73], McCracken et al [74], Hasenbring et al [75] based subgroups on activity-related behavior. As all CLBP patients had a back pain diagnosis in common, it seemed logical to cluster these patients based on their pain characteristics as well as psychological and social factors, as was done by Waddell [7], Hasenbring et al [75], Foster [76], Kamper [77], and Wettstein et al [78] in various previous cluster analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, not much research has been carried out yet in athletes on habitual TS with regard to pain that occurs outside competition or performance. Furthermore, athletes are likely to experience a high number of exercise‐ and career‐related as well as everyday stressors (Heidari, Hasenbring, Kleinert, & Kellmann, ; Heidari et al, ; Rao & Hong, ; Rice et al, ). Thus, it is reasonable to assume TS can play a role in athletes with chronic pain as well, possibly representing a mechanism through which depression and suicidality develop and maintain.…”
Section: Introductionmentioning
confidence: 99%
“…Kallus [24] defines recovery as "an inter-and intraindividual multilevel (e.g., psychological, physiological, social) process in time for the re-establishment of personal resources and their full functional capacity" (p. 42). In light of the fact that deficient recovery has been associated with health problems [25][26][27] and BP in particular [28,29], strengthening this psychological component may exhibit a beneficial influence on BP development. Heidari et al [28] as well as Mierswa and Kellmann [29] have linked patterns of stress and recovery to the occurrence of BP.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the fact that deficient recovery has been associated with health problems [25][26][27] and BP in particular [28,29], strengthening this psychological component may exhibit a beneficial influence on BP development. Heidari et al [28] as well as Mierswa and Kellmann [29] have linked patterns of stress and recovery to the occurrence of BP. The studies suggest that a negative pattern of high stress and low recovery is accompanied by both increased back-related pain intensity and disability [28] and an increased risk to develop BP over time [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation